Exploring the Impact of Mobile Phone Addiction on Psychological Disorders among University Students - Malaika Asif,; Corresponding Author: Khalid Ibn Hassan,; Jesmin Akter, (Al-Qanṭara, 2024)
The pervasive use of smartphones has become an integral part of modern life, yet its excessive use poses serious risks to mental health. This study explores the prevalence of mobile phone addiction and its association with psychological disorders—stress, anxiety, and depression—among university students. Employing a stratified random sampling method, 815 students aged 16–35 years from diverse educational backgrounds were surveyed. Data were gathered through the Smartphone Addiction Scale - Short Version (SAS-SV) and the Depression, Anxiety, and Stress Scale (DASS-21). Findings reveal a concerning 70.4% prevalence of mobile phone addiction, with males (74.5%) showing a higher dependency compared to females (67.4%). Psychological assessments indicate that 78.4% of the participants experienced moderate to severe stress, 80.8% suffered from severe to extremely severe anxiety, and 90.8% exhibited moderate to severe depression. These results highlight mobile phone addiction as a significant predictor of compromised mental health, with severe implications for students' psychological well-being and academic performance. This study underscores the necessity of implementing evidence-based interventions, such as digital detox initiatives, mental health awareness programs, and cognitive-behavioral therapies, to address the burgeoning issue of mobile phone addiction. The findings provide critical insights for policymakers, educators, and mental health practitioners aiming to foster healthier digital habits and improve overall well-being among young adults.